SGLT2 inhibition improves coronary flow velocity reserve and contractility: role of glucagon signaling - Sven O. Göpel; Damilola Adingupu; Jue Wang; Elizaveta Semenova; Margareta Behrendt; Rasmus Jansson-Löfmark; Christine Ahlström; Ann-Cathrine Jönsson-Rylander; V. Sashi Gopaul; Russell Esterline; Li-Ming Gan; Rui-Ping Xiao (Cardiovascular Diabetology, 2024)
Abstract Background SGLT2 inhibitors, a T2DM medication to lower blood glucose, markedly improve cardiovascular outcomes but the underlying mechanism(s) are not fully understood. SGLT2i’s produce a unique metabolic pattern by lowering blood glucose without increasing insulin while increasing ketone body and glucagon levels and reducing body weight. We tested if glucagon signaling contributes to SGLT2i induced improvement in CV function. Methods Cardiac contractility and coronary flow velocity reserve (CFVR) were monitored in ob/ob mice and rhesus monkeys with metabolic syndrome using echocardiography. Metabolic status was characterized by measuring blood ketone levels, glucose tolerance during glucose challenge and Arg and ADMA levels were measured. Baysian models were developed to analyse the data. Results Dapagliflozin improved CFVR and contractility, co-application of a glucagon receptor inhibitor (GcgRi) blunted the effect on CFVR but not contractility. Dapagliflozin increased the Arg/ADMA ratio and ketone levels and co-treatment with GcgRi blunted only the Dapagliflozin induced increase in Arg/ADMA ratio but not ketone levels. Conclusions Since GcgRi co-treatment only reduced the Arg/ADMA increase we hypothesize that dapagliflozin via a glucagon-signaling dependent pathway improves vascular function through the NO-signaling pathway leading to improved vascular function. Increase in ketone levels might be a contributing factor in SGLT2i induced contractility increase and does not require glucagon signaling. Graphical Abstract